2013
DOI: 10.5897/ajb12.1946
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical characterisation and antioxidant activity of some Opuntia ficus-indica varieties grown in North Algeria

Abstract: The composition and the antioxidant activity of the juicy pulp of four Opuntia ficus-indica varieties (green, yellow, orange and red) grown in North Algeria were investigated. The juicy pulp was characterized by a high humidity (87.4 to 89.6%), high pH (6.2 to 6.6), low acidity (0.04 to 0.07%), a few amount of proteins (0.35 to 0.49%) and high amount of solid soluble compounds (12 to 15%). Among the four varieties, the orange variety showed higher values concerning the last parameters. The same variety was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 30 publications
6
13
5
1
Order By: Relevance
“…It is shown to be more attractive for in natura consumption, because they present a higher content of soluble solids and thus a better palatability. Similar results were found by Brito Primo (2008), evaluating fruits in different locations in the state of Paraíba, and by Chougui et al (2013), which found values of 12 to 15 °brix in varieties grown in northern Algeria.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…It is shown to be more attractive for in natura consumption, because they present a higher content of soluble solids and thus a better palatability. Similar results were found by Brito Primo (2008), evaluating fruits in different locations in the state of Paraíba, and by Chougui et al (2013), which found values of 12 to 15 °brix in varieties grown in northern Algeria.…”
Section: Resultssupporting
confidence: 87%
“…The values of pH and acidity found in this work are consistent with those found by Zegbe and Covarrubias (2010). However, Chougui et al (2013) verified that prickly pear have high pH (6.2-6.6) and low acidity (0.04 to 0.07%). Almeida et al (2013), also found low acidity for prickly pear of 0.08 in fruits grown in the state of Bahia.…”
Section: Resultsmentioning
confidence: 95%
“…On the other hand, the seed oil had a higher content of γ-tocopherol (33 ± 3 mg/100 g of total lipids) [ 37 ]. The prickly pear pulp is a good source of ascorbic acid [ 39 , 40 ], and its content ranged from 17 to 46 mg/100 g [ 7 , 15 , 24 , 41 , 42 , 43 , 44 ].…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Sin embargo, para xoconostle estos valores fueron superiores a lo encontrado por Guzmán-Maldonado et al (2010) y por Gallegos-Vázquez et al (2014) con contenidos de 38,1 mg 100 g -1 para 'Cuaresmeño' y de 42,49 mg 100 g -1 para 'Invierno', lo cual es importante debido al potencial que tienen estos compuestos en la disminución de la incidencia de estrés oxidativo y a la posterior aparición de enfermedades crónico-degenerativas (Frankel y German, 2006). La amplia variabilidad que se presentó entre especies y cultivares puede estar relacionada con la ruta de síntesis del ácido ascórbico, la cual difiere ligeramente en su eficiencia entre cultivares, de la misma forma en que influyen factores como las condiciones climáticas y edafológicas, adicionalmente a las condiciones de desarrollo del cultivo, puesto que el género Opuntia al estar adaptado a condiciones limitantes de suelo y agua, podría modificar su composición, principalmente la del fruto (Figueroa-Cares et al, 2010;Chougui et al, 2013).…”
Section: Contenido De áCido Ascórbicounclassified